A Review on the Attainment of Outcome-Based Education Using Educational Data Mining - Yogeswari, Suppiah; Rajermani, Thinakaran (INTI International University, 2022)
This paper aims to conduct a review on the attainment of Outcome-Based Education (OBE) using Educational Data Mining (EDM). It analyses the types of assessment, the type of attainment, and the techniques or tools relevant to Outcome-Based Education (OBE). The Preferred Reporting Items for Systematic Reviews (PRISMA) statement was used as a formal systematic review guideline for data collection. Data was obtained from research studies over the period 2015–2020. The analysis included 25 papers from Scopus, Science Direct, IEEE Xplore, Google Scholar databases. Findings indicated that there were varieties of approaches and techniques applied in evaluating OBE attainment using EDM. Besides that, there was a significant increase in the number of researches related to EDM and OBE attainment in recent years. The type of assessment and attainment were evenly distributed and most of the researches used generalized formula for evaluating OBE attainment. Associate Rule Mining and MS Excel were among the most preferred tools used for the research.